Studi Pertumbuhan Tanaman Sawi (Brassica juncea L.) di Beberapa Konsentrasi Pupuk Organik Cair Supermeses - Tomasoa, Reny (Tropical Small Island Agriculture Management, 2023)
The purpose of this study was to study the growth rate of mustard plants (Brassica juncea L.) at various concentrations of supermes liquid organic fertilizer. At the Faculty of Agriculture, this experiment was carried out in greenhouses. The implementation will take place from August 6 to September 31, 2023. This study was conducted using a one-factor Complete Randomized Design with five treatments level, namely K0 = Control, K1 = 2 cm3/L water, K2 = 4 cm3/L water, K3 = 6 cm3/L water, and K4 = 8 cm3/L water. Plant growth rate, net assimilation rate, root header ratio, and harvest index. The results of the ANOVA test show that the use of cm3 L air fertilizer is the best treatment.